Effect of Ni2+ chelated to the surface of PBFA on the charring flame retardant and smoke suppression properties of epoxy resin. Issue 10 (12th August 2020) - Zhang, Kailun; Wu, Hongjuan; Wu, Ruifang; Yang, Guang; Wang, Tian; Xie, Jixing; Qu, Hongqiang
Abstract: Here, a phosphazene‐based flame retardant (PBFA) containing active amine groups was synthesized by hexachlorocyclotriphosphazene and N‐aminoethylpiperazine and nickel ion (Ni 2+ ) was chelated to the surface of PBFA (named as PBFA‐Ni 2+ ). Incorporation into epoxy resin (EP) with a loading of 6 wt% (named as EP/PBFA‐Ni 2+ ‐6.0), enabled the composite to pass the vertical burning test (UL‐94) V 0 rating. Peak heat release rate and the total smoke release of EP/PBFA‐Ni 2+ ‐6.0 were decreased by 41.02% and 22.74% as measured by cone calorimeter tests. The production rate of CO was inhibited when PBFA‐Ni 2+ was incorporated into EP. Abstract :